Miedo, profecía e identidad nacional en el mundo greco-romano: los oráculos sibilinos (Minerva, 2019)
After some general remarks concerning the main concepts reflected in the title, the author focuses upon the Jewish Sibylline Oracles to illustrate his arguments, selecting Books III and IV as examples of two different (from many points of view), though equally effective, alternatives.